Educação linguística com foco na afetividade : práticas pedagógicas críticas no Programa Idiomas sem Fronteiras - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
In face of the global movements to the internationalization of the universities, many questions about the linguistic education arise. In this work, I pursue to understand how the individual’s subjectivity is formed and its importance in critical linguistic education. I discuss the social and political relationship that interfere in linguistic education while I seek to understand the influence of affectivity in this process. This research took place in the Language without Borders Program at State University of Goiás in Anápolis. It is a qualitative study that considers the subjectivity of the individuals involved in the research. The observations contemplate the aspects proposes by Ludke (1996), such as description of individuals, activities and behaviors. Thus, it has a pos-structuralist approach relating language, subjectivity, social organizations and power (RICHARDSON, 1994, p. 518). In the theory development I find support in the studies of critical literacy of Jordão (2014; 2016; 2019), Pennycook (1999; 2012; 2017), Rajagopalan (2003; 2010; 2013; 2014) that break free from the colonial logic of the linguistic imperialism, Phillipson (1992), Bonnie; Heller (2017) and see the individuals implicated in the linguistic education as social beings, embodied and immerged in emotions that are affected by those ambits in the meaning making. Furthermore, to develop the discussions about subjectivity and linguistic education, I affiliate with the work of Weedon (1997), Woodward (2002) and Fortes (2017). This study has showed the pedagogical praxis embedded in affectivity may help students to break barriers such as shame and fear of speaking in English caused by the discourse of native speakers’ superiority. This research also remarked that linguistic education with focus on the subjectivity and affectivity may transform how the individuals work their agency and how they see each other. Therefore, this context provides a strengthening of the student’s subjectivity and the development of alterity in the classroom environment. Finally, this research points out that we still have hope to bring colors to a linguistic education that until now has showed to be black and white, dichotomic and binary.
Language education with a focus on affectivity: critical pedagogical practices in the languages without borders program
Keywords: Educação linguística - Subjetividade; Educação linguística - Afetividade; Educação linguística - Idiomas sem Fronteiras; Linguistic education - Subjectivity; Linguistic education - Affectivity; Linguistic education - Language without Borders; LINGUISTICA::TEORIA E ANALISE LINGUISTICA; LINGUISTICA::PSICOLINGUISTICA